EVALUATION OF PERFORMANCE BASED BUDGETING AT THE REGIONAL FINANCIAL AGENCY TANAH DATAR - Indra Kartini; Yeni Melia (Jurnal Akuntansi Syariah (JAkSya), 2021)
ABSTRACT                The problem in this research is evaluating the budget preparation procedure in the regional financial institution of Tanah Datar district with the Minister of Home Affairs regulation number 21 of 2011 concerning the guidelines for regional financial management. This study aims to evaluate the budget preparation procedure based on the Minister of Home Affairs regulation number 21 of 2011 concerning guidelines regional financial management in the regional financial agency Tanah Datar. This type of research is field research and the method used is descriptive qualitative. Data collection techniques used are interview and documentation techniques. The data analysis technique used is the comparative method. The results of this study provide evidence that the budget preparation procedure at the flatland district regional financial agency has referred to the Minister of Home Affairs regulation number 21 of 2011 concerning regional financial management quidelines. The outcome of the work plan and budget of the regional flatland district financial agencies for the 2020 fiscal year shows that in general the performance indicators used do not meet the criteria for good performance indicators. Key Words : Evaluation of budget preparation procedures